Application of GIS-Based Frequency Ratio Model to Geoelectric Parameters for Groundwater Potential Zonation in a Basement Complex Terrain - Adeolu Olajide; Ayokunle Adewale Akinlalu; Gregory Oluwole Omosuyi (MO.RI Publishing, 2022)
This study applied a geographic information system (GIS) based frequency ratio (FR) model for groundwater potential assessment in a crystalline basement complex terrain, southwestern, Nigeria. The aim of the study is to investigate the proficiency of the model when applied to geo-electric parameters. Four geo-electrically derived groundwater potential conditioning factors (GPCFs) were used, namely; Aquifer resistivity (AQR), Aquifer thickness (AQT), Coefficient of anisotropy (COA), and Bedrock relief (BED). The well location inventories were partitioned randomly into 70% (45 wells) for model training and 30% (19 wells) for model testing. The frequency ratio model algorithm was used to synthesize the GPCFs to produce the groundwater potential index (GWPI). The estimated GWPI was processed in the GIS environment to produce a groundwater potential zonation map which enabled the demarcation of the study area into five potential zones. The produced FR-based model map was validated through the application of the area under the curve (AUC) approach and spatial attribute comparative scheme (SACS). The AUC validation approach for the FR model showed a 64% success rate and 61% for prediction rate. The quantitative SACS result, based on the well data analysis, established 63% agreement with the insitu well water column thickness map. Similarly, the result of the qualitative SACS established a 71% Agreement. The SACS analysis shows that the FR-based model is a good alternative for prediction of groundwater potential zones even when applied to GWCFs that are geo-electrically derived. Thus, the produced map could form part of decision-making mechanisms for groundwater exploitation and management in the area.